Parametric Stochastic Frontier Approach To Measure Efficiency Pre-And-Post-Merger Bank Syariah Indonesia - Sari, Mella Katrina; Widodo, Saniman; Lestari, Suryani Sri; Widowati, Mustika; Hasanah, Siti (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This research analyses the efficiency of pre-and-post-merger Bank Syariah Indonesia (BSI). This research used a descriptive quantitative analysis method. The population in this research is Islamic banks, which were merged into BSI. The sampling technique was carried out using saturated samples, resulting in the merged of three Islamic Banks, namely Bank Syariah Mandiri (BSM), Bank Negara Indonesia Syariah (BNIS), Bank Rakyat Indonesia Syariah (BRIS), to become BSI. The data used is secondary data in the form of quarterly financial reports for 2019-2022. The research focused on input variables such as total fixed assets, third-party funds, operating costs, and financing. The data analysis techniques used to measure the efficiency of Islamic banks are the Econometric Model (Single Equation Model), Stochastic Frontier Analysis (SFA), and Independent Sample t-test. The result showed that pre-merger, the total fixed asset, total third-party funds, and operating cost as the input variables of the three Islamic Banks were optimal for generating financing. Therefore, the total assets, total third-party funds, and operating costs produced a more optimal impact on the distribution of total financing. It is shown that BSI, both pre-and-post-merger, has generally been efficient in its operational activities. The results of this research complement the theory related to the efficiency level of Islamic banks in terms of the amount of financing as measured by fixed assets, total third-party funds, and operational costs. Practically, the results of this research can be a reference for banks, especially Islamic banks, that will carry out mergers to measure their efficiency level.